1985
DOI: 10.1111/j.1348-0421.1985.tb00798.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Fine Spiral Structures (Spirosomes) by Weak Sonication in Some Bacterial Strains

Abstract: Fine spiral structures (spirosomes) were observed in cell suspensions of five species of bacteria just after weak sonication. The structure is morphologically indistinguishable from the spirosome reported for Lactobacillus species. The molecular weight of the protein of the spirosomes from nine strains was about 94, 000 to 95, 000 as determined by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. The difference in the molecular weight among these spirosomes was not very great, but there were slight di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 12 publications
(15 reference statements)
0
10
0
Order By: Relevance
“…Similar cytoplasmic helical structures were isolated from Acholeplasma laidlawii and were found to be composed of a predominant polypeptide with a molecular weight of 100,000 (16). Matayoshi and Oda (21) also reported that spirosomes morphologically indistinguishable from one another were isolated from nine gram-positive bacteria including Peptostreptococcus productus and Eubacterium aerofaciens after weak sonication and that they were composed of one main protein with a molecular weight of about 94,000 to 95,000. From these findings spirosomes or similar fine spiral structures appear to exist widely as minute cytoplasmic inclusions in both gram-positive and -negative bacteria including spirochetes and mycoplasmas.…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…Similar cytoplasmic helical structures were isolated from Acholeplasma laidlawii and were found to be composed of a predominant polypeptide with a molecular weight of 100,000 (16). Matayoshi and Oda (21) also reported that spirosomes morphologically indistinguishable from one another were isolated from nine gram-positive bacteria including Peptostreptococcus productus and Eubacterium aerofaciens after weak sonication and that they were composed of one main protein with a molecular weight of about 94,000 to 95,000. From these findings spirosomes or similar fine spiral structures appear to exist widely as minute cytoplasmic inclusions in both gram-positive and -negative bacteria including spirochetes and mycoplasmas.…”
mentioning
confidence: 57%
“…We have already found that the spirosomes of L. brevis are composed of a single protein, spirosin, with an apparent molecular weight of about 95,000 as determined by SDS-PAGE (29). The molecular weights of spirosins from various bacteria range from 94,000 to 100,000 (11,16,21). The present comparative study revealed that the spirosins from L. brevis and L. fermentum had an identical molecular weight of about 95,000 and they were cleaved into identical peptide fragments by treatment with NCS or S. aureus V8 protease, whereas the spirosin from L. buchneri possessed a molecular weight of about 96,000 and its peptide map was remarkably different from that of the spirosins from the former two lactobacilli.…”
Section: Antigenicity Of Spirosomesmentioning
confidence: 99%
“…With respect to the localization of spirosome, Kawata et al suggested that it might exist in the cytoplasmic membrane of Lactobacillus (8). On the other hand, Matayoshi and Oda detected the spirosomes by electron microscopy in extracellular fluids of some bacteria which were sonicated weakly but not disrupted at all, suggesting their presence both in the cytoplasm and cell surfaces of these bacteria (15). In our study with Y. enterocolitica by use of MAb, spirosome has proved itself present mostly in the cytoplasm.…”
Section: Localization Of Spirosomementioning
confidence: 99%
“…Spirosome is a spiral inclusion found in various microorganisms, such as Lactobacillus (6), Clostridium (23), Enterobacteriaceae (8,10), Mycoplasma (11), Spirochaeta (3) and others (15). In Lactobacillus, it is composed of protein subunits with a molecular weight of 95 kDa called spirosin (24).…”
mentioning
confidence: 99%
“…These results might indicate differences in the molecular structure of spirosin between Enterobacteriaceae and Lactobacillus, and even among Lactobacillus. Neither MAb reacted with the cell lysate of Bacillus and Pseudomonas, which was related to the findings that there was no spirosome found in these bacteria (6,8). As for the reactivity with V parahaemolyticus, the bacterium might well produce spirosin because it is a Gram-negative facultative anaerobic rod, as is Enterobacteriaceae.…”
Section: Resultsmentioning
confidence: 96%